KETERAMPILAN MENULIS TEKS NARASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA SISWA KELAS VII SMPN 5 TAKALAR - Hanana Muliana; Muhammad Dahlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the ability of 18 students of class VII SMPN 5 Takalar in learning to write narrative texts with a problem-based learning model in the 2023/2024 academic year. Data collection was carried out using test techniques. The data obtained were analyzed using descriptive methods by classifying very high scores, high scores, medium scores and low scores. This type of research is classroom action research consisting of two cycles, namely cycle I with 3 meetings and cycle II with 3 meetings. The researcher only focused on 1 class with a total of 18 students. The learning outcomes of writing narrative texts in cycle I were 59.5 and the learning outcomes of cycle II were 83.8. In cycle I, the category of students who completed were 3 students with a percentage of 16.6%, the category of students who did not complete were 15 students with a percentage of 83.4%. In cycle II, the category of students who completed was 15 students with a percentage of 83.3%, the category of not completing was 3 students with a percentage of 16.6%, meaning that there was an increase of 83.8%. Based on the results of the study above, it can be concluded that the learning outcomes of writing narrative texts of class VII students of SMPN 5 Takalar can be increased by using a problem-based learning model.